Ocular Drug Delivery: Advancements and Innovations - Bo Tian; Evan Bilsbury; Sean Doherty; Sean Teebagy; Emma Wood; Wenqi Su; Guangping Gao; Haijiang Lin (MDPI AG, 2022)
Ocular drug delivery has been significantly advanced for not only pharmaceutical compounds, such as steroids, nonsteroidal anti-inflammatory drugs, immune modulators, antibiotics, and so forth, but also for the rapidly progressed gene therapy products. For conventional non-gene therapy drugs, appropriate surgical approaches and releasing systems are the main deliberation to achieve adequate treatment outcomes, whereas the scope of "drug delivery" for gene therapy drugs further expands to transgene construct optimization, vector selection, and vector engineering. The eye is the particularly well-suited organ as the gene therapy target, owing to multiple advantages. In this review, we will delve into three main aspects of ocular drug delivery for both conventional drugs and adeno-associated virus (AAV)-based gene therapy products: (1) the development of AAV vector systems for ocular gene therapy, (2) the innovative carriers of medication, and (3) administration routes progression.